Aplikasi Tricho-Tithonia dan Biourin Sapi Dalam Menginduksi Pertumbuhan dan Hasil Tanaman Cabai Merah Varietas Lokal Jambi - Eliyanti Eliyanti; Zulkarnain Zulkarnain; Budiyati Ichwan; Mairizal Mairizal; Silva Yulianda (Jurnal Media Pertanian, 2023)
This research aims to test the effectiveness of Tricho-tithonia and Cow Biourin, as well as to obtain the best Tricho-tithonia dose and concentration of bovine biourin in inducing the growth and yield of Jambi Local Variety red chili. The research was carried out at the Faperta-Unja (Teaching and Research Farm) research garden, Mendalo Indah, Jambi Outer City District, Muaro Jambi Regency. The study used a randomized block design (RBD) with two factors. The first factor is the dose of Tricho-tithonia (T), consisting of t1 = 0 tons ha-1, t2 = 10 tons ha-1, and t3 = 20 tons ha-1. The second factor is Biourin Concentration (B), consisting of b1 = 30%, b2 = 40%, and b3 = 50%. The treatment was repeated 3 times, resulting in 27 experimental plots. The variables observed were plant height, number of productive branches, flowering age, number of fruits and fruit weight per plant. Data were analyzed using analysis of variance (ANOVA), followed by using the Least Significant Difference (LSD) test with a level of α=5%. The results that Application of Tricho-tithonia 10-20 tons ha-1can increase plant height, number of productive branches, number of fruits and fruit weight per plant up to almost 3 times, and can induce faster flowering. Meanwhile, spraying the plants with bovine biourin at a concentration of 30-50% had the same effect on all observed variables.Keywords: Capsicum annuum, trichocompost, liquid organic fertilizer, Sustainable agriculture